2020
DOI: 10.3233/jad-200668
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study on the Impact of Arterial Stiffness on the Corpus Callosum, a Key White Matter Tract Implicated in Alzheimer’s Disease

Abstract: Background: Vascular risk factors such as arterial stiffness play an important role in the etiology of Alzheimer’s disease (AD), presumably due to the emergence of white matter lesions. However, the impact of arterial stiffness to white matter structure involved in the etiology of AD, including the corpus callosum remains poorly understood. Objective: The aims of the study are to better understand the relationship between arterial stiffness, white matter microstructure, and perfusion of the corpus callosum in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 83 publications
1
20
0
Order By: Relevance
“…However, although the results of the above studies showed that the DM duration is more important, age was a significant factor affecting the pRNFL change in the DM group in this study. Furthermore, age is well known to play a key role in the etiology of the neurodegenerative diseases, such as Alzheimer's disease and Parkinson's disease, by the increased burden of systemic, chronic, and low-grade inflammatory condition, characterized by persistent www.nature.com/scientificreports/ and non-resolved production of pro-inflammatory mediators [43][44][45] . Therefore, age should not be overlooked as a factor affecting neurodegeneration including DRN.…”
Section: Discussionmentioning
confidence: 99%
“…However, although the results of the above studies showed that the DM duration is more important, age was a significant factor affecting the pRNFL change in the DM group in this study. Furthermore, age is well known to play a key role in the etiology of the neurodegenerative diseases, such as Alzheimer's disease and Parkinson's disease, by the increased burden of systemic, chronic, and low-grade inflammatory condition, characterized by persistent www.nature.com/scientificreports/ and non-resolved production of pro-inflammatory mediators [43][44][45] . Therefore, age should not be overlooked as a factor affecting neurodegeneration including DRN.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, DTI studies looking at the effect of cfPWV on the white matter microstructure showed consistently that several white matter tracts are particularly vulnerable to increased arterial stiffness, among which is the CC, a key white matter tract altered in AD ( Badji et al, 2019 ). Interestingly, cfPWV was recently found to better predict the microstructural integrity of the CC when compared with measures of 24 h SBP, 24 h PP and AIx in participants between 65 and 75 years old ( Badji et al, 2020 ). However, to the best of our knowledge, no other study has yet compared different markers of arterial stiffness on brain integrity, nor has included measures of ASI before the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This stresses the need to find ways to reduce the risk of developing dementia through controlling modifiable factors ( Baumgart et al, 2015 ). Vascular risk factors, such as hypertension and arterial stiffness have been associated with the pathogenesis of dementia, in particular Alzheimer’s disease and vascular dementia through their impact on the white matter ( Singer et al, 2014 ; Badji et al, 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most important contribution of this article is the vendor-neutral solution it provides for multi-center qMRI by significantly reducing inter-vendor variability. This issue has been hampering the standardization of qMRI methods for multi-center clinical trials 60 , validation 61,62 , establishing protocols 17 , applied neuroimaging studies 63 , determining the range of parameters in pathology 64,65 and in health 16,38 , scanner upgrades 49 and even for phantom studies 12,13 . By reducing such variabilities, the VENUS approach can bring qMRI closer to teasing out the true biological variability in quantifying in-vivo tissue microstructure 66 .…”
Section: Discussionmentioning
confidence: 99%